Thinking out of the box—by thinking in other boxes: a systematic review of interventions in early entrepreneurship vs. STEM education research - Joanna Barth; Katrin Muehlfeld (Management Review Quarterly, 2021)
Scholars increasingly converge on the view that entrepreneurship education (EE) should start early during the formative years of individuals' educational careers, ideally in primary and secondary education. They also agree that promotion of attitudinal factors, especially, entrepreneurial self-efficacy (ESE) is of crucial importance. Yet, empirical evidence on effective interventions to foster ESE in early EE is still scarce. Therefore, this study, first, systematically reviews and systematizes this limited literature consisting of eight quantitative studies. Second, in order to develop suggestions for future ESE-oriented interventions in early entrepreneurship education, the study draws on insights from systematically reviewing a second, related yet already more developed literature: research on self-efficacy-oriented interventions in early STEM (science, technology, engineering, and mathematics) education. Third, this study compares the interventions across both research streams in terms of research design, theoretical framework, structure and content of the interventions, and the findings of the studies. As a result, it derives implications for future research on ESE-oriented interventions in early EE: regarding the research design (e.g., use of several treatments); the structure and content of the programs like pedagogical and methodological components (e.g., use of specific learning strategies); analysis of potentially important moderating variables (e.g., gender, social background). Finally, the study discusses the potential for developing cross-disciplinary interventions aimed at simultaneously encouraging self-efficacy in the domains of STEM and entrepreneurship.
Keywords: A21; C90; I20; J24; L26; 650; Entrepreneurship education; Entrepreneurial self-efficacy; Cross-disciplinary research; Primary school; Secondary school; STEM